Analisis Yuridis Sistem Pembuktian dalam Arbitrase Syariah di Indonesia: Perspektif Undang-Undang Nomor 30 Tahun 1999 dan BASYARNAS - Lintang Mahapuan Syahbana Tarekat; Sheira Syaharani Kuan; Sawitri Yuli Hartati S (Journal of Legal, Political, and Humanistic Inquiry, 2025)
This research examines the evidentiary system in Islamic arbitration in Indonesia based on Law Number 30 of 1999 and the practice of the National Sharia Arbitration Board (BASYARNAS). The study aims to analyze the normative framework governing evidence in Islamic arbitration, the types and probative value of evidentiary instruments applied, and the legal standing of BASYARNAS within the national judicial system. Using normative juridical research methods, this study focuses on statutory regulations, doctrinal legal analysis, and the integration of Islamic legal principles with national arbitration law. The findings indicate that the evidentiary system in Islamic arbitration is characterized by procedural flexibility that allows arbitrators to prioritize substantive justice while remaining within the boundaries of positive law. Documentary evidence, witness testimony, expert opinions, party admissions, and electronic evidence are recognized and assessed through a combination of legal validity and Sharia-based ethical considerations. Furthermore, BASYARNAS holds strong legal legitimacy as an arbitration institution, supported by statutory recognition, regulatory frameworks, and its complementary relationship with the Religious Courts in the execution of arbitral awards. This integration strengthens Islamic arbitration as a credible and effective dispute resolution mechanism in Indonesia’s plural legal system.